Perkembangan fungsi eksekutif anak usia pra sekolah: Studi di masa pandemi Covid-19 - Nasa, Amatul Firdausa; Amenike, Diny; Anggreiny, Nila (Universitas Brawijaya, 2022)
The executive function determines whether individuals can perform goal-oriented behaviors. The critical developmental processes of executive function occur during the preschool years. The Covid-19 pandemic increases stress among children and their caregivers. Which consequently hamper the children’s executive function development. The present study examines the development of executive function among preschoolers (2 to 5 years, N = 92) during the Covid-19 pandemic. The results showed that about 12 percent of the sample had developmental problems in their executive function, particularly regarding their emergent metacognition. Children with this developmental problem would find difficulties in initiating, planning, and solving problems independently. Keywords: executive function, preschool children, pandemic, covid-19, child development